Implementation of Scrum for Developing the Data Visualization Dashboard for the PLN UP3 Yogyakarta Project - Widowati, Hestri Apriliani; Cahyono, Andhik Budi (Syntax Corporation Indonesia, 2024)
In the web application development process it is necessary selecting the right method to achieve goals effectively and efficiently. During this time, project development The applications at PLN UP3 Yogyakarta were developed using the waterfall development method. Even there are some projects that are developed without using such development methods moving slowly and not well organized. Therefore, in the PLN UP3 project data visualization dashboard application development project, the scrum method was chosen. The scrum method was chosen Because flexibility, ability for rapid development, and ease of use implemented by all members team developer. The implementation of the Scrum method is carried out according to the stages, namely: setting product goals, creating a product backlog, making sprint planning, conducting sprints, producing increments, conducting sprint reviews, conducting sprint retrospectives, and conducting daily sprints. By using the scrum development method, the SIBER project at PLN can run according to the specified time, according to the timeline, as well produces all the required features.